2016
DOI: 10.1016/j.hlc.2015.10.019
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiac Complications of Methamphetamines

Abstract: Methamphetamines are increasingly popular drugs of abuse in Australia, and are rising in purity. The rising popularity and purity of methamphetamines has notably increased demands upon Australian medical services. Methamphetamines are sympathomimetic amines with a range of adverse effects upon multiple organ systems. Cardiovascular complications are the second leading cause of death in methamphetamine abusers, and there appears to be a high prevalence of cardiac pathology. Cardiovascular pathology frequently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 33 publications
3
74
0
Order By: Relevance
“…34 According to a review of methamphetamine-induced cardiac complications by Paratz et al, dilated, hypertrophic and stress cardiomyopathies are the most common methamphetamine-associated cardiomyopathies. 35 Additionally, intranasal administration of d-amphetamine reportedly lead to a more rapid response compared with oral administration. 5 This study is subject to certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…34 According to a review of methamphetamine-induced cardiac complications by Paratz et al, dilated, hypertrophic and stress cardiomyopathies are the most common methamphetamine-associated cardiomyopathies. 35 Additionally, intranasal administration of d-amphetamine reportedly lead to a more rapid response compared with oral administration. 5 This study is subject to certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…3. Methamphetamine (crystal meth): as for cocaine and amphetamines above, there are reports of cardiomyopathy [73], hypertension, aortic dissection, acute coronary syndromes, pulmonary arterial hypertension and methamphetamine-associated cardiomyopathy [74] and in rat models cardiac pathology [75]. Recommendations as for Cocaine and Ecstasy above.…”
Section: Heartmentioning
confidence: 99%
“…Research has demonstrated that use of methamphetamine can lead to complications with multiple organs and cardiac function (Paratz et al . ), can have a significant impact on cognitive functions (Yu et al . ), and can even lead to changes which seem somewhat similar to those observed in Parkinson's disease (Todd et al .…”
Section: The Main Culpritmentioning
confidence: 99%